Physicochemical Characterization of a Liposomal Formulation Based on Glucosamine and Vitamin D, Commercialized as a Nutritional Supplement - Madrigal Redondo, German (2018)
In the last years, the transport and release mechanism of bioactive compounds has been studied. The liposomes are multivesicular systems that enhance the absorption, stability, and transport of these compounds. The glucosamine is an amino-monosaccharide, it has been associated with many biological activities, but its bioavailability and oral stability are very low. For this reason, the glucosamine formulation in liposomal systems is a good alternative. In this paper, the physicochemical characterization of a liposomal formulation based on glucosamine and vitamin D was realized, this formulation is commercialized as a diet supplement. The determination of pH, degrees Brix, refraction index and specific gravity was realized to characterize the formulation. On the other hand, the structure, size (diameter) and membrane thickness of the liposomes were measured by microscopic observation. From the formulation analysis, it is possible to affirm that the liposomes are multivesicular structures. Also, the external membrane thickness is higher than the membrane thickness of the encapsulated liposomes, indicating the liposomes could be multilamellar structures. The multilamellar and multivesicular structures are related to a high stability, resulting in a beneficial aspect of the formulation. Additionally, the dimension and structure conformation are related with an efficient encapsulation process of the active components, which are glucosamine and vitamin D.